2012
DOI: 10.1371/journal.pone.0048306
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer Elasticity at the Nanoscale: The Need for New Terms

Abstract: Continuum elastic models that account for membrane thickness variations are especially useful in the description of nanoscale deformations due to the presence of membrane proteins with hydrophobic mismatch. We show that terms involving the gradient and the Laplacian of the area per lipid are significant and must be retained in the effective Hamiltonian of the membrane. We reanalyze recent numerical data, as well as experimental data on gramicidin channels, in light of our model. This analysis yields consistent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 42 publications
(349 reference statements)
2
55
0
Order By: Relevance
“…(3) and the corresponding "zeroth-order" models [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] capturing curvature-and fluctuation-mediated protein interactions absorb the molecular details of lipids and membrane proteins into effective material parameters. To provide a more detailed description of bilayer-protein interactions, a number of extensions and refinements of these models have been developed [44,45,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. For instance, the effect of bilayer-protein interactions on the elastic properties of lipid bilayers can be captured [44,81,82,86] by allowing for spatial variations in the values of the elastic bilayer parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(3) and the corresponding "zeroth-order" models [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] capturing curvature-and fluctuation-mediated protein interactions absorb the molecular details of lipids and membrane proteins into effective material parameters. To provide a more detailed description of bilayer-protein interactions, a number of extensions and refinements of these models have been developed [44,45,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. For instance, the effect of bilayer-protein interactions on the elastic properties of lipid bilayers can be captured [44,81,82,86] by allowing for spatial variations in the values of the elastic bilayer parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The minimal model in Eq. (3) can be extended in a variety of ways to account for more detailed properties of lipid bilayers including lipid tilt [48,[75][76][77][78][79], lipid intrinsic curvature [39-42, 45, 70, 71], inhomogeneous deformation of lipid volume and effects of Gaussian curvature on protein-induced bilayer deformations [45,70,71], asymmetric bilayer thickness deformations [45,70,71,80], and protein-induced local modulation of bilayer elastic properties [44,[81][82][83][84][85][86].…”
Section: A Elastic Thickness Deformation Energymentioning
confidence: 99%
See 1 more Smart Citation
“…It states that proteins with a given hydrophobic length insert preferentially into membranes with a similar hydrophobic thickness [4] Many studies of the interaction used as inclusion the antimicrobial peptide (AMP) Gramicidin A (GramA), which is known [5,6] to deform (stretch or compress) host membranes to bring them closer to its own hydrophobic length, so the hydrophobic matching mechanism is likely relevant. This perturbation of the membrane prole induces between the GramA pores in bilayers with various compositions [7] a repulsive interaction that can be explained based on a complete elastic model [8].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Bitbol et al (2012) have shown that the thickness gradient in the membrane observed in nanoscale studies can be explained by keeping the terms in the Hamiltonian involving the gradient and Laplacian of the area per lipid. This is consistent with what was previously derived in Deseri et al (2008) from a dimension reduction procedure.…”
Section: Introductionmentioning
confidence: 99%